Feasibility of Busulfan Melphalan and Stem Cell Rescue After 131I-MIBG and Topotecan Therapy for Refractory or Relapsed Metastatic Neuroblastoma: The French Experience. Issue 6 (August 2018) - Ferry, Isabelle; Kolesnikov-Gauthier, Hélène; Oudoux, Aurore; Cougnenc, Olivier; Schleiermacher, Gudrun; Michon, Jean; Bogart, Emilie; Chastagner, Pascal; Proust, Stéphanie; Valteau-Couanet, Dominique; Defachelles, Anne-Sophie
Abstract : High-risk neuroblastoma is characterized by poor long-term survival, especially for very high-risk (VHR) patients (poor response of metastases after induction therapy). The benefits of a tandem high-dose therapy and hematologic stem cell reinfusion (HSCR) have been shown in these patients. Further dose escalation will be limited by toxicity. It is thus important to evaluate the efficacy and tolerability of the addition of new agents such as 131 I-MIBG (131Iode metaiodobenzylguanidine) to be combined with high-dose therapy in the consolidation phase. We report the feasibility of busulfan/melphalan (BuMel) after 131 I-MIBG therapy with HSCR in patients with refractory or relapsed metastatic neuroblastoma. From November 2008 to March 2015, 9 patients received BuMel after 131 I-MIBG therapy and topotecan. The main toxicity was digestive with only 1 patient developing grade 4 sinusoidal obstructive syndrome. Seven patients are alive at a median follow-up of 25 months. Among them, 2 are in ongoing complete remission and 1 in ongoing stable disease. These results suggest that BuMel with HSCR can be administered safely 2 months after 131 I-MIBG therapy associated with topotecan for VHR patients. This strategy will be compared with tandem high-dose chemotherapy (thiotepa and busulfan-melphalan), followed by HSCR in the upcoming SIOPEN VHR Neuroblastoma Protocol.